Book Reviews (Historia, 2021)
1. Gutsche, T.: The History and Social Significance of Motion Pictures in South Africa, 1850.1940, pp. XXVI, 404, 66 ill.,2. D. Bax. Zuid Afrika's eerste open bare verzameling op het gebied van Kunst en Etnologie. Schenkers: Yon Dessin, James Cook, James King. Pp. 156, 32 afbeeldings. 3. Ramsay, P. H. (red.): The Price Revolution in Sixteenth-Century England, Methuen,Londen, 1.971. Pp. 181., bibl. 4. Baraitser, M. & A. Obholzer: Cape Country Furniture, a pictorial survey of reginal styles, materials and techniques in the Cape, pp. xviii, 286, 891 ill., A. A. Balkema; Kaapstad, 1971, R20.5. Jiirgen Deininger: Der Politische Widerstand gegen rom in Griechenland 217-86 v. Chr. Walter de Gruyter, Berlyn en New York 1971. 279 pp.6. Nicholls, C. S.: The S}vahili Coast. Politics, Diplomacy and Trade on the East African Littoral, 1798-1856. Pp. 419. Allen & Unwin, 1971. RI2,007. P. & R. Liversage: Ludwig Krebs, Cape King Naturalist to the King of Prussia, 1792-1844, pp. XV, 304, 16 ill, Kaapstad, A. A. Balkema, 1971. R7.50